THE ISSUE OF UNIVERSITY–LABOR MARKET COOPERATION IN THE HIGHER EDUCATION SYSTEM OF THE NETHERLANDS (EDUCATION IN THE 21ST CENTURY, 2025)
Today, higher education and the labor market are viewed not only as separate educational and occupational systems but also as interconnected socio-economic institutional systems, whose effective operation contributes to national development and the establishment of an innovative economy. Education serves not only as a means of knowledge transfer but also as a strategic instrument for training labor-market-competitive professionals.The higher education system of the Netherlands, encompassing both applied (HBO) and academic/research-oriented (WO) tracks, operates based on these approaches by ensuring students’ integrated professional and practical competencies. The system’s effectiveness is enhanced through strategic cooperation among universities, employers, and state bodies, as reflected in the national Strategic Agenda for Higher Education and Research 2015–2025. Mechanisms such as work placements, dual learning programs, graduate engagement, and sectoral planning are fundamental in ensuring students’ employability and the socio-economic efficiency of higher education.The Dutch experience emphasizes that higher education must closely align with labor market demands, thereby increasing graduates’ competitiveness, reducing unemployment risks, and providing a reliable foundation for continuous professional development and innovative activity. Within the scope of this study, the main models of university–labor market cooperation in the Netherlands have been analyzed, existing challenges identified, the impact of education on the overall labor market structure examined, and potential improvements outlined.
Keywords: Netherlands; higher education; labor market; university–labor market cooperation; academic education; employability; human capital